Art-therapeutic technologies based on musical folklore, forwarded to overcome psychological problems - Grigorieva Elena Ivanovna, Ovsyannikova Vera Alexandrovna,; Morozova Ekaterina Alexandrovna, Katz Maria L’vovna,; Mikhailovna, Scherbinina Valentina (Opción, 2019)
The article is devoted to art-therapeutic technologies based on musical folklore, improvisation and playing music, aimed at solving problems in the physical and spiritual development of children via considering the methods of Karl Orff and Shinichi Suzuki, in particular, the concepts of their upbringing systems. As a result, musical games accompanied by instruments allow you to perceive music by different senses through tactile contact, muscular sensations, hearing and sight. In conclusion, the use of art therapy technologies in music lessons contributes to the preservation of the schoolchild’s health, and also develops the musical, creative and spiritual abilities of children.